The prostitution of sexuality - Barry, Kathleen (New York University Press, 1995)
In 1979, Kathleen Barry's landmark book, Female Sexual Slavery, pulled back the curtain on a world of abuse prostitution that shocked the world. Documenting in devastating detail the lives of street prostitutes and the international traffic in women, Barry's work was called powerful and compassionate by Adrienne Rich and a courageous and crusading book that should be read everywhere by Gloria Steinem. The Los Angeles Times found it a powerful work filled with disbelief, outrage, and documentation ... sexual bondage shackles women as much today as it has for centuries.